No limits blow the cap off your capacity - Maxwell, John C. (New York Center Street, 2017)
We often treat the word capacity as if it were a natural law of limitation. Unfortunately most of us are much more comfortable defining what we perceive as off limits rather than what's really possible. Could it be that many of us have failed to expand our potential because we have allowed what we perceive as capacity to define us? What if our limits are not really our limits?
Keywords: Self-actualization (Psychology)